Whole body vibration for chronic patellar tendinopathy: A randomized equivalence trial - Rieder, Florian; Wiesinger, Hans-Peter; Herfert, Jürgen; Lampl, Katrin; Hecht, Stefan; Niebauer, Josef; Maffulli, Nicola; Kösters, Alexander; Müller, Erich; Seynnes, Olivier R. (Frontiers in Physiology, 2022)
Purpose: Whole body vibration (WBV) triggers anabolic responses in various tissues, including tendons, without requiring high force production. In this waitlist-controlled equivalence trial, we tested its clinical effectiveness as an alternative treatment for patellar tendinopathy against conventional heavy slow resistance training (HSR). Methods: Thirty-nine patients were randomized to either 3 months of WBV training (n = 13), HSR training (n = 11), or a waitlist control (WLC) group (n = 15). In a partly cross-over design, 14 patients of the WLC group were redistributed to one of the two intervention groups (5 in WBV, 9 in HSR). Pre- and post-intervention testing included pain assessments (VAS), functional limitations (VISA-P), knee extension strength and tendon morphological, mechanical and material properties. Follow-up measurements (VAS, VISA-P) were performed in the WBV and HSR groups six months after the intervention. Results: Comparisons with the WLC group revealed significant improvements in VISA-P and VAS scores after HSR (41%, p = 003; 54%, p = .005) and WBV (22%, p = .022; 56%, p = .031) training. These improvements continued until follow-up (HSR: 43%, 56%; WBV: 24%, 37%). Pre-post improvements in VAS scores were equivalent between WBV and HSR groups but inconclusive for the VISA-P score and all pre-test to follow up comparisons. The mid-tendon cross-sectional area was significantly reduced after WBV (-5.7%, p = .004) and HSR (-3.0%, p = .004) training compared to WLC although the equivalence test between interventions was inconclusive. Conclusion: Whole body vibration improved symptoms typically associated with patellar tendinopathy. This type of intervention is as effective as HSR against maximum pain, although equivalence could not be confirmed for other variables. The beneficial responses to WBV and HSR treatments persisted for 6 months after the end of the intervention. This clinical trial is registered at the DRKS (DRKS00011338) https://www.drks.de/drks_web/setLocale_EN.do